1977 supplement to the statistical yearbook and the monthly bulletin of statistics : methodology and definitions - United Nations (New York : United Nations, 1972)
The supplement provides more detailed note for the statistical series published in the Statistical Yearbook and the Monthly Bulletin of Statistics than is possible in the footnotes to the tables shown in the publications. Particular reference is made to the scope, coverage, methods of compilation, definitions and other factors affecting the international comparability of statistics.
Issued with United Nations publications sales number.
Includes bibliographical references: p. 416-428.
oif 05/03/2019
Ref.
Keywords: Statistical services; Statistics; Social history; Economic history